Seroprevalence and associated risk factors o epizootic hemorrhagic disease virus in cattle from the northern region of Peru: first serological report. - Ponce, K. (2025)
Epizootic hemorrhagic disease virus (EHDV) is a vector-borne pathogen that affects both wild and domestic ruminants. Climate influences vector-borne diseases by driving vector migration to new areas, where they spread the virus. However, the lack of surveillance in some areas hinders accurate assessment the true disease burden. This study aimed to determine the seroprevalence of EHDV and associated risk factors in cattle from the northern region of Peru in 2022. Blood serum samples were collected from 578 cattle in the departments of Tumbes, Piura, Lambayeque, Cajamarca, and La Libertad and analyzed using cELISA. The overall EHDV seroprevalence was 17.82% (95% confidence interval 14.78-21.19). The highest proportion of seropositive animals was observed in two deparments closest to the equator, Piura and Tumbes (50%), followed by Lambayeque (39.1%) and Cajamarca (11.08%). In addition, the highest seroprevalence was found at temperatures ≤20°C (50.46%), wind speeds ≤3 m/sec (31.43%), and altitudes ≤1,260 masl (37.28%), with a significant decrease at higher elevations (P<0.05). After adjusting for temperature, the odds of EHDV seropositivity were significantly lower in cattle from areas located at >2,000 to ≤3,290 masl (Odds ratio [OR]=0.15) and >3,290 (OR=0.07), compared to those from the reference altitude category of ≤1,260 masl. Similarly, after adjusting for altitude, cattle from deparments with temperatures >20°C had significantly lower odds of seropositivity (OR=0.17) compared to those exposed to temperatures ≤20°C. This study reports anti-EHDV antibodies in cattle from northern Peru for the first time, highlighting associations with bioclimatic factors.